Synchrotron X-ray fluorescence imaging evidence of biogenic mercury identified in a burial in colonial Antigua. (June 2015) - Swanston, Treena; Varney, Tamara; Coulthard, Ian; George, Graham N.; Pickering, Ingrid J.; Murphy, Reg; Cooper, David M.L.
Abstract: A mass spectroscopic analysis of bone samples from 17 individuals once buried in a Royal Naval Hospital cemetery (1793–1822) in Antigua revealed a high level of mercury (Hg) in one individual. While the toxic properties of Hg are now recognized, this metal was used for centuries to treat ailments such as syphilis and yellow fever. Synchrotron radiation X-ray fluorescence imaging (XFI) was employed to determine whether the Hg was present in the bone as a result of environmental contamination or due to biogenic uptake. The XFI study revealed that only a localized subset of the osteons within a 2.5 mm by 1.5 mm scan contained Hg – a finding consistent with biogenic uptake. The near-edge portion of the X-ray absorption spectrum was used to determine that the Hg was present in the bone tissue as an inorganic mercuric sulfide. Highlights: A bone sample from a colonial cemetery in Antigua contained a high level of mercury. Synchrotron imaging was used to determine that the uptake of mercury was biogenic. The mercury was in the form of an inorganic mercuric sulfide. This toxic metal was used as a medicine in colonial times.